Feminist mobilization, claims making and policy change: Insights from Asia - Nitya Rao; Paola Cagna (United Nations Research Institute for Social Development (UNRISD), 2016)
This paper aims to understand how policy change for women's rights occurs, and what factors and conditions facilitate non-state actors' influence over policy processes. It argues that policy change is a complex and iterative process, and explores the range of actors that mobilize for/against gender equality policy change, with a particular focus on women's movements. The paper provides insights on how women interact with other actors and how they articulate their claims to effectively influence the policy process. It also explores why certain domains of women's rights remain at the margins of political agendas, while others receive more attention. The analysis is based on a comparative research of women's claims making processes in three Asian countries (China, India and Indonesia) and on three different issues: violence against women, domestic workers' labour rights, and unpaid care work. The paper sets out the rationale, aims and theoretical framework of the research, and discusses the key insights.
Additional information: Prepared for the UNRISD project on: When and Why Do States Respond to Women's Claims? Understanding Gender-Egalitarian Policy Change in Asia
Keywords: 330; policy change; China; India; Indonesia; women's movements; violence against women; domestic workers; unpaid care work